Gender Studies in Islam (2000–2025): Research Fronts, Hotspots, and Conceptual Shifts in the Literature - Judijanto, Loso (Westscience Press, 2026)
In this article, the world research front in the area of gender studies in Islam is considered for the period from 2000 to 2025. Bibliometric and network analysis methods have been used for exploring author collaborations, citation patterns, and keyword relations. In result, it was found that this research network has a complex structure, including significant participation of countries like the US and the UK, as well as developing involvement of Muslim countries such as Malaysia, Turkey, and Indonesia. Citation analysis revealed the most influential literature and themes, including themes on veiling, identity, Islamophobia, and socio-political aspects of gender. Keyword analysis showed that the key concepts included